(untitled) (LACCEI, 2024)
There is the possibility of being born without a lower or upper limb, or that this also arises through a surgical act. When facing a patient who requires an amputation, it is necessary to think not only about saving life but also about preserving good possibilities of independence and social reintegration. Lower limb prostheses only fulfill the function of replacing the limb and adding a tool to provide better support, which does not help to create a normal movement of the joints, nor do they present a type of cushioning that helps in impact against the ground, causing harm and discomfort. This research aims to design, characterize, construct, and control a transfemoral prosthesis prototype with magneto-rheological damper to determine its functionality for aiding patients in Honduras. It was possible to design and control a transfemoral prosthesis prototype. Equally, the material (Aluminum) chosen, and the design that was presented meets the appropriate characteristics to resist a weight of an average person from Honduras of 80 kg, since a force of 400 N was applied in each of the parts.